Ethics and Affects in the Fiction of Alice Munro (Palgrave Studies in Affect Theory and Literary Criticism, 2018)
Ethics and Affects in the Fiction of Alice Munro explores the representation of embodied ethics and affects in Alice Munro's writing. The collection illustrates how Munro's short stories powerfully intersect with important theoretical trends in literary studies, including affect studies, ethical criticism, age studies, disability studies, animal studies, and posthumanism. These essays offer us an Alice Munro who is not the kindly Canadian icon reinforcing small-town verities who was celebrated and perpetuated in acts of national pedagogy with her Nobel Prize win; they ponder, instead, an edgier, messier Munro whose fictions of affective and ethical perplexities disturb rather than comfort. In Munro's fiction, unruly embodiments and affects interfere with normative identity and humanist conventions of the human based on reason and rationality, destabilizing prevailing gender and sexual politics, ethical responsibilities, and affective economies. As these essays make clear, Munro's fiction reminds us of the consequences of everyday affects and the extraordinary ordinariness of the ethical encounters we engage again and again. .